Does Organizational Green Culture Impact Competitive Advantage and Green Performance with Mediation of Green Innovation? (Journal of Social Sciences Review, 2024)
The competitive landscape is undergoing a rapid transformation because of the increasing public concern regarding the natural environment, which is compelling firms to implement green innovation strategies. Although there has been not much study on green innovation, the concept has been acknowledged by numerous manufacturing firms. By the logic of natural resource-based view theory (NRBV), the objective of this paper is to empirically construct and test a theoretical model that examines the impact of organizational green culture (OGC) on green innovation (GI), competitive advantage (CA) and green performance (GP). It also investigates the influence of GI on CA and GP. This model elucidates how green innovation mediates these associations. The researchers gathered data from 319 manufacturing enterprises in Punjab, Pakistan. The data were analyzed using smartPLS 3.2.9 (variance-based software). This paper employs a questionnaire to collect primary data from managers. The study's results indicate that OGC substantially predicted GI, CA, and GP. In addition, GI has a substantial effect on GP and CA. The results also indicate that GI partially mediates the relationship between OGC-CA and OGC-GP. Some limitations are providing directions for future investigations.
Keywords: Organizational Green Culture; Competitive Advantage; Green Performance; Green Innovation